Penerapan model problem based learning berbantuan media audiovisual dalam meningkatkan kemampuan komunikasi matematis siswa kelas VII - Wahyuni, Tania; Yuliani, Anik; Nurfauziah, Puji (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2024)
This research was motivated by the low mathematical communication skills of high school students, this research was carried out at SMP Dharma Kartini in grade VII as many students. The instrument used was a mathematical communication ability description test. The purpose of this research is to improve students' mathematical communication skills and the achievement of students' learning goals using the Problem Based Learning (PBL) model assisted by audiovisual media. The data from the study were processed using 2 independent samples using the normality test and the Monte Carlo test. The results of the analysis showed that grade VII junior high school students who used the Problem Based Learning (PBL) model with the help of audiovisual media got a better increase in mathematical communication skills compared to students who used the conventional learning model. Furthermore, students who get an improvement in learning using the Problem Based Learning (PBL) model assisted by audiovisual media also experience achievement in learning objectives.